EDUKASI SADARI SEBAGAI UPAYA PENINGKATAN PENGETAHUAN DAN KETERAMPILAN DALAM DETEKSI DINI KANKER PAYUDARA - Damayanti, Ajeng Dea; Mardiana, Novi; Anggraeni, Ernawati; Pangestuningtyas, Trisna (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2024)
Breast cancer is the uncontrolled growth of cells in the breast. The emergence of cancer cells occurs as a result of mutations or abnormal changes in the genes that are responsible for maintaining cell growth and keeping them normal (healthy). Breast cancer is a type of malignant disease that is very feared by women because breast cancer is in second place after cervical cancer. Breast cancer can be detected early by self-examination of the breast, clinical examination and mammography examination to find out early. BSE examination can be started early until it becomes a routine habit to detect breast cancer early. The aim of this service is to provide information about early detection of breast cancer by conducting breast self-examination. The method used in this community service activity begins with an opening and introduction of the resource persons, then continues with the delivery of health education material, a question and answer session to the participants and finally closing